The Field Hospital's Responsibility For Patient Autonomy When A Medical Dispute Occurs - Wijaya, Deni (Indonesian Red Crescent Humanitarian Journal, 2024)
Public institutions that have a focus on managing and providing patient services to the community are hospitals. Field hospitals (field hospitals) are service units created to assist the function of referral health services (outpatient, inpatient, emergency unit, operating room, laboratory , etc.) which is carried out in emergency conditions. The aim of this research is to find out how to protect patients in field hospitals in the event of a medical dispute, and who is responsible if a medical dispute occurs in the field hospital. This research method uses a qualitative phenomenological method aimed at describing or explaining a person's personal experience, including the experience of relationships with other people, using literature study as a data collection procedure. The results of the research are that the Field Hospital has not yet regulated or there are no regulations in the event of a medical dispute. in field hospitals, resulting in harm to patients, and in Law Number 17 of 2023, there are no regulations regarding Field Hospitals, which means it creates a legal vacuum, so far there has been no legal review regulating responsibility for medical disputes in hospitals field because the author conducted this literature study research.